2018
DOI: 10.1098/rsos.180604
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenetic mechanism of the acquisition of the dinosaur-type acetabulum

Abstract: Understanding morphological evolution in dinosaurs from a mechanistic viewpoint requires the elucidation of the morphogenesis that gave rise to derived dinosaurian traits, such as the perforated acetabulum. In the current study, we used embryos of extant animals with ancestral- and dinosaur-type acetabula, namely, geckos and turtles (with unperforated acetabulum), and birds (with perforated acetabulum). We performed comparative and experimental analyses, focusing on inter-tissue interaction during embryogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“….resembled early ancestral/developmental morphologies (that is, instances of localized paedomorphosis): the broad, flat avian ischium resembled the early embryonic state and that of ancestral archosaurian [my emphasis] condition more than it did the intermediate dinosaurian conditions." It should be noted in passing that although studies like those of Egawa et al [122], Griffin et al [20], and many others [127][128][129][130] exhibit a surprisingly Haeckelian recapitulationism, the data they provide are more reasonably interpreted in accordance with von Baer's principles of simple conservativism of early embryos, without the orthogenetic implications of Haeckel's recapitulation of past ancestors. In the words of Paul Ehrlich and colleagues: "The resemblance of early vertebrate embryos is readily explained without resort to mysterious forces compelling each individual to reclimb its phylogenetic tree."…”
Section: Hip Joint Morphology In Extant Birds (Neornithes)mentioning
confidence: 77%
See 3 more Smart Citations
“….resembled early ancestral/developmental morphologies (that is, instances of localized paedomorphosis): the broad, flat avian ischium resembled the early embryonic state and that of ancestral archosaurian [my emphasis] condition more than it did the intermediate dinosaurian conditions." It should be noted in passing that although studies like those of Egawa et al [122], Griffin et al [20], and many others [127][128][129][130] exhibit a surprisingly Haeckelian recapitulationism, the data they provide are more reasonably interpreted in accordance with von Baer's principles of simple conservativism of early embryos, without the orthogenetic implications of Haeckel's recapitulation of past ancestors. In the words of Paul Ehrlich and colleagues: "The resemblance of early vertebrate embryos is readily explained without resort to mysterious forces compelling each individual to reclimb its phylogenetic tree."…”
Section: Hip Joint Morphology In Extant Birds (Neornithes)mentioning
confidence: 77%
“…In the case of quail, not only were the acetabula imperforate throughout embryogenesis, but even the adult acetabulum may be almost closed (Figure 5d). Egawa et al [122] further suggested that a dinosaur-type perforated acetabulum arises from acetabular cartilage loss in chicken embryos. They linked acetabular perforation in "non-avian" dinosaurs and birds (represented in their study by Struthio and Gallus) with high susceptibility to bone morphogenetic protein (BMP) antagonists and Wnt ligands [122].…”
Section: Hip Joint Morphology In Extant Birds (Neornithes)mentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, in adults of extinct dinosaurs the relative size of acetabular perforation gradually diminished in size towards ornithurans [ 11 ]. Embryonic joint spaces have special mesenchymal layers called the interzone (IZ), which spans the acetabulum in embryonic saurian hip joints, and IZ-expressed molecules (canonical Wnt ligands) cause the perforation of the avian acetabulum [ 84 ]. Therefore, that the evolutionary reduction of adults' acetabular size probably reflects a reduction of the IZ range and thus, that of the acetabulum of embryos.…”
Section: Resultsmentioning
confidence: 99%